Analisis Kesalahan Siswa dalam Menyelesaikan Soal Bilangan Berpangkat Bulat Positif dan Negatif - Lastari, Dwi Wirda; Kartini, Kartini (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
This study aims to analyzes alsos describestype of error the students did based on Kastolan to solveproblem with positive and negative integers. The subjects in this study there are 16 students from class VII Pondok Pesantren MTs As-Sakinah, Kampar Regency. The type of research is descriptive qualitative. Data collections technics carried out from the form of written tests also interviews. Written test is arranged in a forms of a description of 5 questions. The data analysis techniques carried out were: correcting the results of students' answers; identify and analyze errors that students did to answer questions based on types of Kastolan errors; count percentages of errors on every items in every types of error; percentage results are categorized by error percentage; the counted data will be analyses descriptively with interpreting results of calculating the percentage of student errors; and draw conclusion. The results of the analysis of student errors, it was obtained that 18.2% of students made conceptual errors with very low error categories, 42.4% of students made procedural errors with sufficient error categories, and 39.4% of students made arithmetical errors with low error categories.